2012
DOI: 10.1093/eurjhf/hfr159
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension predicts all‐cause mortality in patients with heart failure: a retrospective cohort study

Abstract: AimsThe presence of pulmonary hypertension (PH) in left ventricular systolic dysfunction (LVSD) and symptomatic heart failure is an ominous sign. There are insufficient data regarding the risk conferred by increasing severity of PH in patients with heart failure. Methods and resultsWe performed a record linkage study in Tayside, Scotland (population 400 000) utilizing the Tayside echocardiogram database (.50 000 echocardiograms) maintained by the Health Informatics Centre (HIC). Data sets from the HIC include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 19 publications
8
42
0
Order By: Relevance
“…18 By quantifying the FMR, which is poorly assessed by standard qualitative methods, we ensured that through the matching process patients with and without PH had similar degrees of FMR so that we could ascertain for the first time that the PH link to morality is not a surrogate for FMR. Furthermore, our subgroup analysis, which could not be performed in previous studies because of lack of FMR ascertainment, [7][8][9]33 shows that PH is equally predictive of excess mortality with or without FMR, confirming the independent role of PH in predicting survival. Similarly, although an independent link between LVDD and mortality is not entirely established, by obtaining quantitative measures of LVDD, we were also able for the first time to demonstrate that PH is not a surrogate of LVDD.…”
Section: Mechanisms Of Ph In Lvsdsupporting
confidence: 68%
“…18 By quantifying the FMR, which is poorly assessed by standard qualitative methods, we ensured that through the matching process patients with and without PH had similar degrees of FMR so that we could ascertain for the first time that the PH link to morality is not a surrogate for FMR. Furthermore, our subgroup analysis, which could not be performed in previous studies because of lack of FMR ascertainment, [7][8][9]33 shows that PH is equally predictive of excess mortality with or without FMR, confirming the independent role of PH in predicting survival. Similarly, although an independent link between LVDD and mortality is not entirely established, by obtaining quantitative measures of LVDD, we were also able for the first time to demonstrate that PH is not a surrogate of LVDD.…”
Section: Mechanisms Of Ph In Lvsdsupporting
confidence: 68%
“…However, pulmonary hypertension is possibly an important comorbidity, which can result from LVSD32, 33, 34 or IPF 35, 36. Whether due to LVSD37, 38 or IPF,39, 40, 41 pulmonary hypertension is associated with significantly increased morbidity and mortality. In addition to the postulated role of pulmonary hypertension, there is evidence demonstrating extensive redistribution of pulmonary blood flow in individuals with hemodynamically significant LVSD, underscoring a complex heart–lung interaction 42.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] PH is a disease with devastating effects on quality of life and life expectancy, and is a potent cause of heart failure (HF) in general. [7,[9][10][11][12] Indeed, one autopsy study from South Africa identified PH as one of the commonest causes of death, accounting for RESEARCH 31% of all cardiovascular deaths. [13] The Pan African Pulmonary Hypertension Cohort (PAPUCO) study was established to investigate the epidemiology, causes and natural history of PH in Africa.…”
Section: Researchmentioning
confidence: 99%